Preparation method of composite coating of electric arc additive manufacturing alloy and composite coating
By preparing a copper-titanium intermetallic compound composite coating with titanium carbide and titanium oxide composite reinforced composite coating on the surface of the arc additive manufacturing alloy, and using plasma spraying technology to prepare ceramic particles in stages, the problems of limited types and high cost of silk materials when used in the wear resistance field in the prior art are solved, and higher wear resistance and application flexibility are achieved.
Patent Information
- Application Number
- CN202411671391.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-28
AI Technical Summary
When existing arc additive manufacturing alloys are used in the wear-resistant field, the types of wire materials are limited and costly, making it difficult to meet specific application needs.
Plasma spraying technology is used to prepare titanium carbide and titanium oxide composite composite coatings on the surface of arc additive manufacturing alloys, and TiC and TixOy ceramic particles are prepared in stages through solidification reaction and solid gas reaction to achieve independent regulation of the ceramic phase.
It significantly improves the wear resistance of arc additive manufacturing alloys, enhances the hardness and toughness of the coating, and expands its application range in the field of wear resistance.
Smart Images

Figure CN119710527A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of additive manufacturing technology, and more specifically to a composite coating preparation method and composite coating of an arc additively manufactured alloy. Background Art
[0002] Arc additive manufacturing is a technology that uses electric arc as a heat source to manufacture complex metal components by melting and depositing metal materials layer by layer. It has the advantages of high material utilization, high manufacturing efficiency and low process cost, and is widely used in aerospace, shipbuilding, automotive industry and energy fields. At present, arc additive manufacturing mainly uses alloy wires, and its performance is limited by the limited variety of commercial wires and the high cost of customized wires, making it difficult to meet specific application requirements such as wear resistance. Therefore, developing composite coating technology to improve the wear resistance of arc additive manufacturing alloy surfaces and expand its application scope has become an important research direction.
[0003] Ceramic particle reinforced composite coatings significantly improve the wear resistance, corrosion resistance and high temperature resistance of metal surfaces by dispersing high-hardness ceramic particles in the matrix, and are widely used in aerospace, automobile manufacturing, petrochemical and mold industries. Commonly used reinforcing particles include oxides (Al2O3, ZrO2), carbides (TiC, WC) and nitrides (Si3N4), which are widely used to enhance the wear resistance of metals and alloys due to their high hardness, high temperature resistance and chemical stability. A Chinese patent (application number: CN201510236852.5) discloses a method for preparing a copper-based titanium carbide / aluminum oxide particle reinforced composite material, which uses the high temperature of copper liquid to trigger the self-propagating reaction of pre-set powder to prepare a TiC / Al2O3 multiphase hard coating. A Chinese patent (application number: CN202211415057.9) discloses a method for preparing a self-generated dual-phase ceramic particle reinforced copper-based composite coating, which prepares a self-generated TiC-TiB2 particle reinforced copper-based coating by laser cladding pre-set materials to improve the wear resistance of the coating. However, the above methods all use a high-temperature heat source to trigger the reaction of pre-fabricated solid-phase powder to prepare multiphase ceramic particles. The two ceramic phases are generated at the same time, and it is difficult to control the content, particle size and distribution of any ceramic phase. Due to the extremely high reaction temperature and short time, the control of the in-situ synthesis process of multiphase ceramics has always been a difficulty in the development of in-situ preparation technology. At present, no one at home or abroad has proposed a technology for independently controlling the ceramic phase reaction process in stages during high-energy heat source processing.
[0004] Plasma spraying technology is a widely used coating preparation technology that can use the high temperature of the plasma jet to synthesize ceramic phase in situ during the spraying process, thereby preparing ceramic particle-reinforced composite coatings. The ceramic particles prepared by plasma spraying are evenly distributed and small in size, reaching micro / nano sizes.
[0005] Cu-Ti alloy has attracted extensive attention as an ultra-high strength conductive material and is a common wear-resistant alloy material. In the phase diagram of the Cu-Ti binary system, there are a series of intermetallic compound phases (CuTi, CuTi2), which have high hardness and can significantly improve the wear resistance of the coating as a matrix material. Copper-titanium based composite coatings with ceramic particles such as titanium carbide and titanium oxide as reinforcement phases can significantly improve the wear resistance of the metal matrix. At present, there has been no research at home and abroad on the in-situ preparation of titanium carbide-titanium oxide composite reinforced CuTi intermetallic compound-based composite coatings by plasma spraying. Summary of the invention
[0006] In this embodiment, a composite coating preparation method and a composite coating of an arc additively manufactured alloy are provided to solve the problems of limited available wire and high cost in the related art when arc additively manufactured alloys are applied in the wear-resistant field.
[0007] In a first aspect, an embodiment of the present invention provides a method for preparing a composite coating of an arc additively manufactured alloy, the method comprising: Weighing powders according to a ratio of 75% to 95% copper-titanium powder and 25% to 5% carbon powder, and grinding them to obtain a mixed powder, mixing the mixed powder with deionized water, a dispersant, a binder, and a defoamer, stirring with a mechanical stirrer to obtain a suspension slurry, sending the suspension slurry into a centrifugal spray granulator through a peristaltic pump, and drying with high-temperature air to obtain a nearly spherical composite powder; The surface of the arc additive manufacturing alloy is sandblasted, and the powder is fed into a high-temperature plasma jet using a pneumatic powder feeding device. The high-temperature plasma jet is used to melt the copper-titanium powder and wrap the carbon powder to form flying droplets. The plasma jet draws oxygen into the liquid phase to form oxygen-rich droplets. The carbon powder in the flying droplets dissolves into the liquid phase and reacts with titanium to form TiC particles. The plasma jet accelerates the droplets to hit the alloy surface, the droplets cool and deform, and the liquid phase precipitates TixOy particles during high-speed solidification. The TiC particles and the TixOy particles are co-distributed in the CuTi intermetallic compound matrix formed by liquid phase solidification to form a composite coating.
[0008] In an optional embodiment, the copper-titanium powder includes a copper-titanium alloy powder, a combination of a copper single substance powder and a titanium single substance powder, and a mixture of a copper-titanium alloy powder and a single substance powder.
[0009] In an optional embodiment, the carbon powder includes graphite or coke.
[0010] In an optional embodiment, the spraying power of plasma spraying is 25-45 kW, the spraying current is 350-650 A, the argon flow rate is 10-40 NLPM, and the powder feeding gas in the pneumatic powder feeding device is argon with a flow rate of 4 NLPM.
[0011] In an optional embodiment, oxygen is added to the plasma jet through a powder feeding gas and an external pipeline during the plasma spraying process.
[0012] In an optional embodiment, the arc additive manufacturing alloy includes steel, aluminum alloy, copper alloy, titanium alloy, and nickel-based alloy.
[0013] In an optional embodiment, copper-titanium powder and carbon powder are weighed according to a ratio and then put into a planetary ball mill for wet grinding to reduce the powder size to less than 10 μm to obtain a mixed powder, which is then dried in a vacuum drying oven. Compared with the prior art, the method for preparing a composite coating of an arc additively manufactured alloy of the present invention has the following beneficial effects: In order to solve the problem of limited available wire and high cost when arc additive manufacturing alloys are used in the wear-resistant field, a new copper-titanium intermetallic compound-based composite coating reinforced with titanium carbide and titanium oxide is proposed to improve the wear resistance of arc additive manufacturing alloys. Copper-titanium intermetallic compounds have higher hardness than metal matrix, but are more brittle and difficult to be used as wear-resistant coatings alone. Titanium oxide and titanium carbide, as ceramic reinforcement particles, have high hardness and can significantly improve the wear resistance of the coating. At the same time, the addition of micro / nanoscale ceramic particles can play a role in crack bridging and crack deflection, improve the toughness of copper-titanium intermetallic compounds, and thus improve the wear resistance of the coating; Solid-solid reaction and solid-gas reaction are simultaneously introduced into plasma spraying. By utilizing the differences in reactant types and product melting points, a two-stage reaction in the plasma spraying process is proposed, thereby achieving independent regulation of the content, particle size and distribution of the reaction products TiC and TixOy in different reaction stages. This method greatly improves the flexibility of the preparation of multiphase ceramic particle reinforced composite coatings.
[0014] In a second aspect, an embodiment of the present invention provides a reinforced composite coating of an arc additively manufactured alloy, which is prepared by the method for preparing a composite coating of an arc additively manufactured alloy described in the first aspect.
[0015] In an optional embodiment, the composite coating includes a ceramic reinforcement phase and an intermetallic compound matrix phase, the ceramic reinforcement phase is TiC and TixOy, and the intermetallic compound matrix phase is a CuTi phase.
[0016] In an optional embodiment, the sizes of TiC and TixOy are between 10 and 1000 nm.
[0017] Compared with the prior art, the beneficial effects of the arc additively manufactured alloy reinforced composite coating of the present invention are the same as the arc additively manufactured alloy composite coating preparation method described in the first aspect, so it will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 It is a flow chart of a method for preparing a composite coating of an alloy by arc additive manufacturing in an embodiment of the present invention; Figure 2 This is a SEM photograph of the Cu-Ti-C composite powder morphology in an embodiment of the present invention.
[0020] Figure 3 It is the XRD spectrum of the Cu-Ti-C composite powder in the embodiment of the present invention.
[0021] Figure 4 This is a SEM photograph of the cross-section microstructure of the TiC-TixOy-CuTi coating in an embodiment of the present invention.
[0022] Figure 5 : This is the XRD spectrum of the TiC-TixOy-CuTi coating in the embodiment of the present invention. DETAILED DESCRIPTION
[0023] In order to more clearly understand the purpose, technical solutions and advantages of the present application, the present application is described and illustrated below in conjunction with the accompanying drawings and embodiments.
[0024] Unless otherwise defined, the technical terms or scientific terms involved in this application shall have the general meaning understood by people with general skills in the technical field to which this application belongs. The words "one", "a", "the", "these" and the like in this application do not indicate a quantitative limitation, and they may be singular or plural. The terms "include", "comprise", "have" and any variants thereof involved in this application are intended to cover non-exclusive inclusions; for example, a process, method and system, product or device comprising a series of steps or modules (units) is not limited to the listed steps or modules (units), but may include unlisted steps or modules (units), or may include other steps or modules (units) inherent to these processes, methods, products or devices. The words "connect", "connected", "coupled" and the like involved in this application are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect. The "multiple" involved in this application refers to two or more. "And / or" describes the association relationship of associated objects, indicating that there may be three relationships, for example, "A and / or B" may mean: A exists alone, A and B exist at the same time, and B exists alone. Generally, the character " / " indicates that the objects associated with each other are in an "or" relationship. The terms "first", "second", "third", etc. in this application are only used to distinguish similar objects and do not represent a specific ordering of the objects.
[0025] In an embodiment of the present invention, a method for preparing a composite coating of an arc additively manufactured alloy is provided. Figure 1 is a flow chart of the method for preparing a composite coating of an arc additively manufactured alloy of the present invention, such as Figure 1 As shown, the process includes the following steps: S12. Weigh powders according to the ratio of 75% to 95% copper-titanium powder and 25% to 5% carbon powder, and grind them to obtain mixed powders, mix the mixed powders with deionized water, dispersant, binder, and defoaming agent, and stir them with a mechanical stirrer to obtain a suspension slurry, send the suspension slurry into a centrifugal spray granulator through a peristaltic pump, and dry it with high-temperature air to obtain a nearly spherical composite powder; specifically, weigh copper-titanium powder and carbon powder according to the ratio, put them into a planetary ball mill for wet grinding to reduce the powder size to less than 10 μm, obtain a mixed powder, and dry it in a vacuum drying oven.
[0026] It should be noted that the copper-titanium powder includes copper-titanium alloy powder, a combination of copper powder and titanium powder, and a mixture of copper-titanium alloy powder and titanium powder. The carbon powder includes graphite or coke or other forms of carbon.
[0027] S14. Sandblast the surface of the arc additive manufacturing alloy, use a pneumatic powder feeding device to feed the powder into a high-temperature plasma jet, use the high-temperature plasma jet to melt the copper-titanium powder, wrap the carbon powder, form flying droplets, and the plasma jet draws oxygen into the liquid phase to form oxygen-rich droplets. The carbon powder in the flying droplets dissolves into the liquid phase and reacts with titanium to form TiC particles; the spraying power of plasma spraying is 25-45kW, the spraying current is 350-650A, and the argon flow rate is 10-40NLPM. The powder feeding gas in the pneumatic powder feeding device is argon with a flow rate of 4NLPM. During the plasma spraying process, oxygen is added to the plasma jet through the powder feeding gas, an external pipeline or other means. Add oxygen to the plasma jet.
[0028] S16. The plasma jet accelerates the droplets to impact the alloy surface. The droplets cool and deform. TixOy particles are precipitated from the liquid phase during high-speed solidification. The TiC particles and the TixOy particles are co-distributed in the CuTi intermetallic compound matrix formed by liquid phase solidification to form a composite coating.
[0029] The arc additive manufacturing alloys include steel, aluminum alloy, copper alloy, titanium alloy, and nickel-based alloy.
[0030] Example 1 Copper-titanium alloy powder and graphite powder were mixed in a mass ratio of 95% and 5%, and wet-milled in a planetary ball mill with anhydrous alcohol as the medium, a ball-to-material ratio of 10:1, a rotation speed of 300 rpm, and a time of 8 hours. After ball milling, the mixture was dried in a vacuum drying oven for 4 hours to obtain a mixed powder; The mixed powder was mixed with deionized water, aqueous dispersant A15 solution, binder 10% PVA solution and defoamer n-butanol, and mechanically stirred for 20 minutes to obtain a suspension slurry. The suspension slurry was sent to a centrifugal spray granulator through a peristaltic pump, and spherical composite powder was obtained by high-temperature air drying. The granulation process parameters were: air inlet temperature 260°C, air outlet temperature 100°C, and atomizing disk speed 10000rpm. The surface of the aluminum alloy manufactured by arc additive manufacturing is sandblasted with corundum sand; the composite powder is fed into the plasma jet through a pneumatic powder feeding device, and is heated and accelerated by the plasma jet and impacts the surface of the aluminum alloy to form a coating. The plasma spraying process parameters are as follows: spraying power 25kW, spraying current 500A, argon flow rate 40NLPM, powder feeding gas is argon, and the flow rate is 3NLPM. The obtained coating has a dense structure and a strong bonding force with the substrate. The average surface Rockwell hardness is 90.5HR15N and the average cross-sectional nanoindentation hardness is 7.7GPa.
[0031] Example 2 Copper powder, titanium powder and coke powder were mixed in a mass ratio of 37.5%, 37.5% and 25%, and wet-milled in a planetary ball mill with anhydrous alcohol as the medium, a ball-to-material ratio of 5:1, a rotation speed of 300 rpm, and a time of 8 hours. After ball milling, the mixture was dried in a vacuum drying oven for 4 hours to obtain a mixed powder; The mixed powder was mixed with deionized water, aqueous dispersant A15 solution, binder 10% PVA solution and defoamer n-butanol, and mechanically stirred for 20 minutes to obtain a suspension slurry. The suspension slurry was sent to a centrifugal spray granulator through a peristaltic pump, and spherical composite powder was obtained by high-temperature air drying. The granulation process parameters were: air inlet temperature 260°C, air outlet temperature 100°C, and atomizing disk speed 10000rpm. The surface of the copper alloy manufactured by arc additive manufacturing is sandblasted with corundum sand; the composite powder is fed into the plasma jet through a pneumatic powder feeding device, and is accelerated by the plasma jet and impacts the surface of the copper alloy to form a coating. The plasma spraying process parameters are as follows: spraying power 35kW, spraying current 650A, argon flow rate 40NLPM, and the powder feeding gas is argon with a flow rate of 3NLPM. The obtained coating has a dense structure and a strong bonding force with the substrate. The average surface Rockwell hardness is 92.4HR15N and the average cross-sectional nanoindentation hardness is 8.2GPa.
[0032] Embodiment 3: Copper-titanium alloy powder and graphite powder were mixed in a mass ratio of 75% and 25%, and wet-milled in a planetary ball mill with anhydrous alcohol as the medium, a ball-to-material ratio of 5:1, a rotation speed of 300 rpm, and a time of 8 hours. After ball milling, the mixture was dried in a vacuum drying oven for 4 hours to obtain a mixed powder; The mixed powder was mixed with deionized water, aqueous dispersant A15 solution, binder 10% PVA solution and defoamer n-butanol, and mechanically stirred for 20 minutes to obtain a suspension slurry. The suspension slurry was sent to a centrifugal spray granulator through a peristaltic pump, and spherical composite powder was obtained by high-temperature air drying. The granulation process parameters were: air inlet temperature 260°C, air outlet temperature 100°C, and atomizing disk speed 10000rpm. The surface of the titanium alloy manufactured by arc additive manufacturing was sandblasted with corundum sand. A gas pipe with a length of 10 cm, a proximal radius of 5 cm, a distal radius of 10 cm and an external air inlet was installed at the mouth of the plasma spray gun. Oxygen was introduced with a flow rate of 10 NLPM. The composite powder was sent into the plasma jet through a pneumatic powder feeding device, and the composite powder was heated and accelerated by the plasma jet and impacted the titanium alloy substrate to form a coating. The plasma spraying process parameters were as follows: spraying power 35 kW, spraying current 650 A, argon flow rate 40 NLPM, and the powder feeding gas was argon with a flow rate of 3 NLPM. The obtained coating has a dense structure, the TixOy phase content inside the coating is increased, the bonding force with the substrate is strong, the average surface Rockwell hardness is 91.8HR15N, and the average cross-sectional nanoindentation hardness is 8.5GPa.
[0033] Based on the above embodiments, refer to Figures 2 to 5 As shown, from Figure 2 It can be seen that the spray granulated CuTi powder and carbon powder (graphite) are fully mixed and agglomerated into nearly spherical powder; Figure 3 It can be seen that the composite powder is mainly composed of carbon (graphite), CuTi2, and CuTi phases. Figure 4 It can be seen that the coating has a typical plasma sprayed layer structure. Figure 5 It can be seen that CuTi, TiO, Ti2O and TiC phases are formed in the coating, indicating that solid-solid / solid-gas reactions between titanium and carbon, and titanium and oxygen occur during the plasma spraying process.
[0034] In order to solve the problem of limited available wire and high cost when arc additive manufacturing alloys are used in the wear-resistant field, a new copper-titanium intermetallic compound-based composite coating reinforced with titanium carbide and titanium oxide is proposed to improve the wear resistance of arc additive manufacturing alloys. Copper-titanium intermetallic compounds have higher hardness than metal matrix, but are more brittle and difficult to be used as wear-resistant coatings alone. Titanium oxide and titanium carbide, as ceramic reinforcement particles, have high hardness and can significantly improve the wear resistance of the coating. At the same time, the addition of micro / nanoscale ceramic particles can play a role in crack bridging and crack deflection, improve the toughness of copper-titanium intermetallic compounds, and thus improve the wear resistance of the coating; Solid-solid reaction and solid-gas reaction are simultaneously introduced into plasma spraying. By utilizing the differences in reactant types and product melting points, a two-stage reaction in the plasma spraying process is proposed, thereby achieving independent regulation of the content, particle size and distribution of the reaction products TiC and TixOy in different reaction stages. This method greatly improves the flexibility of the preparation of multiphase ceramic particle reinforced composite coatings.
[0035] An embodiment of the present invention further provides an arc additively manufactured alloy reinforced composite coating, which is prepared by using the above-mentioned arc additively manufactured alloy reinforced composite coating preparation method.
[0036] The composite coating comprises a ceramic reinforcement phase and an intermetallic compound matrix phase, wherein the ceramic reinforcement phase is TiC and TixOy, and the intermetallic compound matrix phase is a CuTi phase.
[0037] The TiC and Ti x O y The size is between 10 and 1000 nm.
[0038] The composite coating is deposited on the surface of the arc additive manufacturing alloy, including a ceramic reinforcement phase and an intermetallic compound matrix phase; the ceramic reinforcement phase is TiC and TixOy, with a size between 10 and 1000 nm, and the Ti-O atomic ratio in TixOy can be adjusted to one or more combinations of Ti3O, Ti2O, TiO, and TiO2 by controlling the oxygen content; the intermetallic compound matrix phase is a CuTi phase; TiC and TixOy are prepared by two-stage reactions during plasma spraying, in which TiC is prepared by a solid-solid reaction of titanium and carbon in the first stage, and TixOy is prepared by a solid-gas reaction of titanium and oxygen in the second stage, and the two-stage reactions are independently controllable to achieve independent adjustment of the content, particle size and distribution of TiC and TixOy.
[0039] Based on the above, the main problem to be solved by the present invention is to realize the independent regulation of the content, particle size and distribution of two ceramic phases in the copper-titanium-based wear-resistant coating reinforced by in-situ multiphase ceramics during the preparation of composite coatings on the surface of arc additive manufacturing alloys. To this end, the present invention simultaneously introduces solid-solid reaction and solid-gas reaction into plasma spraying, and prepares TiC by solid-solid reaction between solid-phase titanium and solid-phase carbon, and prepares TixOy by solid-gas reaction between solid-phase titanium and gas-phase oxygen. By utilizing the differences in melting points and reactant types of TiC and TixOy, the two reactions are carried out in stages, and solid-solid reaction is realized in the flying droplets of spraying to prepare TiC, and solid-gas reaction is realized in the process of spraying impact arc additive manufacturing alloys to prepare TixOy, thereby separating the two ceramic phase reaction processes and realizing independent regulation of the content, particle size and distribution of TiC and TixOy.
[0040] In addition, the present invention uses CuTi intermetallic compound phase as the matrix of the coating and uses multiphase ceramics as the reinforcing phase. The CuTi intermetallic compound has a higher basic hardness than metal, and the multiphase ceramics has a toughening effect on the intermetallic compound phase, thereby further improving the wear resistance of the coating.
[0041] The present invention uses arc additive manufacturing alloy as a deposition substrate, copper-titanium powder and carbon powder as raw materials, and prepares composite powder by spray granulation. Plasma spraying of the composite powder realizes the reaction between titanium and carbon, titanium and oxygen, thereby depositing a copper-titanium-based composite coating containing titanium carbide and titanium oxide. The solid-solid-solid-gas two-stage reaction plasma spraying method proposed in the present invention can independently regulate the reaction between powder and powder, powder and oxygen in stages during the spraying process, obtain micro / nano titanium carbide and titanium oxide with controllable content, particle size and distribution in the coating, and improve the wear resistance of the arc additive manufacturing alloy.
[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a composite coating of an arc additively manufactured alloy, characterized in that: The composite coating preparation method comprises: Weighing powders according to a ratio of 75% to 95% copper-titanium powder and 25% to 5% carbon powder, and grinding them to obtain a mixed powder, mixing the mixed powder with deionized water, a dispersant, a binder, and a defoamer, stirring with a mechanical stirrer to obtain a suspension slurry, sending the suspension slurry into a centrifugal spray granulator through a peristaltic pump, and drying with high-temperature air to obtain a nearly spherical composite powder; The surface of the arc additive manufacturing alloy is sandblasted, and the powder is fed into a high-temperature plasma jet using a pneumatic powder feeding device. The high-temperature plasma jet is used to melt the copper-titanium powder and wrap the carbon powder to form flying droplets. The plasma jet draws oxygen into the liquid phase to form oxygen-rich droplets. The carbon powder in the flying droplets dissolves into the liquid phase and reacts with titanium to form TiC particles. The plasma jet accelerates the droplets to hit the alloy surface, the droplets cool and deform, and the liquid phase precipitates TixOy particles during high-speed solidification. The TiC particles and the TixOy particles are co-distributed in the CuTi intermetallic compound matrix formed by liquid phase solidification to form a composite coating.
2. The method for preparing a composite coating of an arc additively manufactured alloy according to claim 1, characterized in that: The copper-titanium powder includes a copper-titanium alloy powder, a combination of a copper single substance powder and a titanium single substance powder, and a mixture of a copper-titanium alloy powder and a single substance powder.
3. The method for preparing a composite coating of an arc additively manufactured alloy according to claim 1, characterized in that: The carbon powder includes graphite or coke.
4. The method for preparing a composite coating of an arc additively manufactured alloy according to claim 1, characterized in that: The spraying power of plasma spraying is 25-45 kW, the spraying current is 350-650 A, the argon flow rate is 10-40 NLPM, and the powder feeding gas in the pneumatic powder feeding device is argon with a flow rate of 4 NLPM.
5. The method for preparing composite coating of arc additively manufactured alloy according to claim 1, characterized in that: During the plasma spraying process, oxygen is added to the plasma jet through the powder feeding gas and external pipeline.
6. The method for preparing composite coating of arc additively manufactured alloy according to claim 1, characterized in that: The arc additive manufacturing alloys include steel, aluminum alloy, copper alloy, titanium alloy, nickel-based alloy gold.
7. The method for preparing composite coating of arc additively manufactured alloy according to claim 1, characterized in that: Copper-titanium powder and carbon powder are weighed according to a ratio and then put into a planetary ball mill for wet grinding to reduce the powder size to less than 10 μm to obtain a mixed powder, which is then dried in a vacuum drying oven.
8. An arc additively manufactured alloy reinforced composite coating, characterized in that: The composite coating is prepared by the method for preparing the alloy by arc additive manufacturing as described in any one of claims 1 to 7.
9. The reinforced composite coating of the arc additively manufactured alloy according to claim 8, characterized in that: The composite coating comprises a ceramic reinforcement phase and an intermetallic compound matrix phase, wherein the ceramic reinforcement phase is TiC and TixOy, and the intermetallic compound matrix phase is a CuTi phase.
10. The reinforced composite coating of arc additively manufactured alloy according to claim 9, characterized in that: The sizes of the TiC and TixOy are between 10 and 1000 nm.
Citation Information
Patent Citations
Preparation method of copper-based titanium carbide / aluminum oxide surface particle strengthening composite material
CN104942268A
Preparation method of authigenic biphase ceramic particle reinforced copper-based composite coating
CN115627474A